Internal flow behaviour and microstructural evolution of the bobbin-FSW welds: thermomechanical comparison between 1xxx and 3xxx aluminium grades - Abbas Tamadon; Pons, Dirk John; Don Clucas; Sued, Mohammad Kamil (Walter de Gruyter GmbH, 2021)
The influences of processing parameters and tool feature on the microstructure of AA1100 and AA3003 aluminium alloys were investigated using bobbin friction stir welding (BFSW). The research includes flow visualization and microstructural evolution of the weld texture using the metallographic measurement method. Results indicated that the operational parameters of the welding (e.g. feed rate, rotating speed) and the geometry of the tool can directly affect the flow patterns of the weld structure. The microscopic details revealed by the optical and electron microscope imply the dynamic recrystallization including grain refinement and precipitation mechanisms within the stirring zone of the weld region. The microscopic observations for the weld samples show a better performance of the fully-featured tool (tri-flat threaded pin and scrolled shoulders) compared to the simple tool without inscribed surface features. The fully-featured tool resulted in a more uniform thermomechanical plastic deformation within the weld structure along with the precipitation hardening and the homogeneity of the microstructure.